Inclusion complexes of β-cyclodextrin with tricyclic drugs: an X-ray diffraction, NMR and molecular dynamics study - Castiglione, Franca; Ganazzoli, Fabio; Malpezzi, Luciana; Mele, Andrea; Panzeri, Walter; Raffaini, Giuseppina (Beilstein Journal of Organic Chemistry, 2017)
Tricyclic fused-ring cyclobenzaprine (1) and amitriptyline (2) form 1:1 inclusion complexes with β-cyclodextrin (β-CD) in the solid state and in water solution. Rotating frame NOE experiments (ROESY) showed the same geometry of inclusion for both 1/β-CD and 2/β-CD complexes, with the aromatic ring system entering the cavity from the large rim of the cyclodextrin and the alkylammonium chain protruding out of the cavity and facing the secondary OH rim. These features matched those found in the molecular dynamics (MD) simulations in solution and in the solid state from single-crystal X-ray diffraction of 1/β-CD and 2/β-CD complexes. The latter complex was found in a single conformation in the solid state, whilst the MD simulations in explicit water reproduced the conformational transitions observed experimentally for the free molecule.
Keywords: amitriptyline; β-cyclodextrin; crystal structure; cyclobenzaprine; molecular dynamics simulations; NOE

(untitled) - Mele, A.; Raffaini, G.; Ganazzoli, F.; Juza, M.; Schurig, V. (Carbohydr. Res., 2003)

(untitled) - Malpezzi, L.; Fronza, G.; Fuganti, C.; Mele, A.; Brückner, S. (Carbohydr. Res., 2004)

(untitled) - Ali, M. S.; Rub, M. A.; Khan, F.; Al-Lohedan, H. A.; Kabir-Ud-Din (J. Mol. Liq., 2012)

(untitled) - Cano, J.; Rodriguez, A.; Aicart, E.; Junquera, E. (J. Inclusion Phenom. Macrocyclic Chem., 2007)

(untitled) - Wei, W.; Zhang, Z. J.; Ju, H. X. (Chromatographia, 2004)

(untitled) - Junquera, E.; Romero, J. C.; Aicart, E. (Langmuir, 2001)

(untitled) - Georgiou, M. E.; Koupparis, M. A.; Georgiou, C. A. (Analyst, 1999)

(untitled) - Valsami, G. N.; Koupparis, M. A.; Macheras, P. E. (Pharm. Res., 1992)

(untitled) - Dalla Cort, A.; Mandolini, L.; Pasquini, C.; Schiaffino, L. (New J. Chem., 2004)

(untitled) - Casarotto, M. G.; Craik, D. J. (J. Pharm. Sci., 2001)

(untitled) - Altomare, A.; Burla, M. C.; Camalli, M.; Cascarano, G. L.; Giacovazzo, C.; Guagliardi, A.; Moliterni, A. G. G.; Polidori, G.; Spagna, R. (J. Appl. Crystallogr., 1999)

The Measurement of Molecular Complex Stability - Connors, K. A. (Binding Constants, 1987)

(untitled) - Desvaux, H.; Berthault, P.; Birlirakis, N.; Goldman, M.; Piotto, M. (J. Magn. Reson., Ser. A, 1995)

InsightII (Accelrys Inc., 2000)

(untitled) - Dauber-Osguthorpe, P.; Roberts, V. A.; Osguthorpe, D. J.; Wolff, J.; Genest, M.; Hagler, A. T. (Proteins: Struct., Funct., Genet., 1988)

(untitled) - Raffaini, G.; Ganazzoli, F.; Malpezzi, L.; Fuganti, C.; Fronza, G.; Panzeri, W.; Mele, A. (J. Phys. Chem. B, 2009)

(untitled) - Raffaini, G.; Ganazzoli, F. (J. Inclusion Phenom. Macrocyclic Chem., 2007)

(untitled) - Raffaini, G.; Ganazzoli, F. (J. Inclusion Phenom. Macrocyclic Chem., 2013)

(untitled) - Raffaini, G.; Ganazzoli, F. (Chem. Phys., 2007)

(untitled) - Raffaini, G.; Ganazzoli, F. (J. Phys. Chem. B, 2010)